2006
DOI: 10.2144/000112218
|View full text |Cite
|
Sign up to set email alerts
|

Exonuclease-mediated ELISA-like assay for detecting DNA-binding activity of transcription factors: measurement of activated NF-κB

Abstract: This paper describes an exonuclease-mediated enzyme-linked immunosorbent assay (ELISA)-like assay (EMEA) for detecting the DNA binding activity of nuclear factor kappaB (NF-kappaB). For EMEA, a special double-stranded DNA (dsDNA)-coupled plate was first prepared by immobilizing a DNA probe on an N-oxysuccinimide ester-coated plate. The immobilized DNA probe, which was internally labeled with digoxigenin (DIG)-dT contained a NF-kappaB binding consensus sequence for capturing activated NF- kappaB in analyzed sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…# 07-200-585) at a concentration of 25 pmol in a 100 μl volume per each well in oligonucleotide binding buffer (50 mM Na 3 PO 4 , pH 8.5, 1 mM EDTA) and washed extensively (Supplemental Figure 1S-C). Five pmol of the antisense oligo was added and a dsDNA was formed as in [50]. Plate-bound DNA was incubated with up to 30 ng/well total of homodimers or heterdimers of the nuclear receptors (PPARα, RXRα or LXRα) (if heterodimers like PPARα+LXRα, then in equal concentrations) for 20 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…# 07-200-585) at a concentration of 25 pmol in a 100 μl volume per each well in oligonucleotide binding buffer (50 mM Na 3 PO 4 , pH 8.5, 1 mM EDTA) and washed extensively (Supplemental Figure 1S-C). Five pmol of the antisense oligo was added and a dsDNA was formed as in [50]. Plate-bound DNA was incubated with up to 30 ng/well total of homodimers or heterdimers of the nuclear receptors (PPARα, RXRα or LXRα) (if heterodimers like PPARα+LXRα, then in equal concentrations) for 20 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Taking advantage of the (T) 14 linker, the sense oligo was immobilized inititially to an N-oxysuccinimide ester-coated plate at a concentration of 200 pmol in a 100 μl volume per each well in oligonucleotide binding buffer (50 mM Na 3 PO 4 , pH 8.5, 1 mM EDTA) and washed extensively. The antisense oligo was added and a dsDNA was formed as in 37 . Plate-bound DNA was incubated with 30 ng/well PPARα for 20 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…No matter which kit is used, the optimal detection of TF activity ranges between 0.5 and 100 μg of nuclear extract. Wang et al [ 20 ] showed that the detection range was between 0.625 and 10 μg of nuclear extract. In our study, the sensitivity of TF activity was quantified as about 0.05–2 μg of nuclear extract.…”
Section: Discussionmentioning
confidence: 99%